Model reference resilient control for the helicopter with time‐varying disturbance. (17th July 2019) - Chen, Mou; Li, Yankai
Summary: In this paper, the problem of model reference resilient control is investigated for the helicopter system with the time‐varying disturbance and unmeasurable states. Firstly, a disturbance observer and a state observer are built to estimate the time‐varying disturbance and unmeasurable states. Then, combining the methods of model reference control and disturbance observer–based control, the state feedback robust resilient control scheme and the dynamic output feedback robust resilient control method are proposed, respectively. Under the two developed robust resilient control schemes, sufficient conditions are obtained to guarantee that the helicopter system asymptotically tracks the reference model with H ∞ performance. Finally, simulation results are presented to show the effectiveness of the model reference resilient control method.